A model measuring therapeutic inertia and the associated factors among diabetes patients: A nationwide population‐based study in Taiwan. (28th July 2014) - Huang, Li‐Ying; Shau, Wen‐Yi; Yeh, Hseng‐Long; Chen, Tsung‐Tai; Hsieh, Jun Yi; Su, Syi; Lai, Mei‐Shu
Abstract This article presents an analysis conducted on the patterns related to therapeutic inertia with the aim of uncovering how variables at the patient level and the healthcare provider level influence the intensification of therapy when it is clinically indicated. A cohort study was conducted on 899, 135 HbA1c results from 168, 876 adult diabetes patients with poorly controlled HbA1c levels. HbA1c results were used to identify variations in the prescription of hypoglycemic drugs. Logistic regression and hierarchical linear models (HLMs) were used to determine how differences among healthcare providers and patient characteristics influence therapeutic inertia. We estimated that 38.5% of the patients in this study were subject to therapeutic inertia. The odds ratio of cardiologists choosing to intensify therapy was 0.708 times that of endocrinologists. Furthermore, patients in medical centers were shown to be 1.077 times more likely to be prescribed intensified treatment than patients in primary clinics. The HLMs presented results similar to those of the logistic model. Overall, we determined that 88.92% of the variation in the application of intensified treatment was at the within‐physician level. Reducing therapeutic inertia will likely require educational initiatives aimed at ensuring adherence to clinical practice guidelines in the care of diabetes patients.